Community intervention programs for sex offenders: A systematic review - Barros, Sofia; Oliveira, Cláudia; Araújo, Eduardo; Moreira, Diana; Almeida, Fernando; Santos, Anita (Frontiers in Psychiatry, 2022)
Sexual violence is a phenomenon that negatively impacts the victims’ physical and psychological health and well-being. Sex offenders tend not to take responsibility for their actions, have difficulties in emotion regulation and impulse control, paraphilias or other disorders, so they are a difficult group to treat. In addition, the available psychological treatment programs tend to have inconsistent and, sometimes, undesirable results. This systematic review aimed to analyse the recidivism rates of sex offenders treated in community settings. According to the PRISMA guidelines, a systematic search in three databases, EBSCOhost, PubMed, and Web of Science, and a manual search was performed. A total of 319 empirical studies using quantitative methodologies were identified, 27 of which were selected for full-text analysis. In the end, 15 studies were included, published between 1996 and 2020. The objectives, intervention approach, instruments used, and the main results and conclusions were extracted from each study. The studies explored different types of sex offenders, such as: violent sex offenders (e.g., rapists), child abusers, and child abusers with pedophilia (and/or other paraphilias). Results showed that most of the programs had a cognitive-behavioral approach (n = 13). Overall, the interventions appear to be effective in reducing recidivism rates, and some of them led to improvements in other outcomes, such as cognitive distortions, accepting responsibility, victim awareness and empathy, emotional regulation, and offense supportive attitudes. Limitations and implications for future studies were discussed.